Hygienic-sanitary quality of ready-to-eat salmon sashimi (Salmo Salar) (Research, Society and Development, 2021)
Fifty sashimi samples from 5 restaurants were characterized for enumeration of Aerobic Psychrotrophic Heterotrophic Bacteria (APHB) and Aerobic Mesophilic Heterotrophic Bacteria (AMHB), Enterobacteriaceae, coliforms at 45ºC (thermotolerant coliforms), coagulase-positive Staphylococci, presence of Vibrio parahaemolyticus and Salmonella sp., and determination of hydrogen potential (pH) and total volatile basic nitrogen (TVB-N). The bacterial isolates were evaluated for their resistance profile to the antimicrobial agents Penicillin, Ampicillin, Cefoxitin, Cefotaxime, Amikacin, Gentamicin, Tetracycline, and Trimethropim-sulfamethoxazole. The results showed that APHB, AMHB and coagulase-positive Staphylococci counts and the determination of pH and TVB-N were in accordance with national and international standards adopted as safe limits for consumption. In contrast, the Enterobacteriaceae and thermotolerant coliforms counts and presence of Salmonella sp. and V. parahaemolyticus were in disagreement with those standards, raising concern about the hygienic-sanitary quality of sashimi. The Staphylococcus aureus and V. parahaemolyticus isolates showed resistance to Penicillin, Ampicillin, Cefoxitin, Cefotaxime, Tetracycline, Gentamicin, and Amikacin, while the Salmonella sp. isolate showed no resistance to all the antimicrobial agents studied. The results showed that 48% of the samples were fit for consumption while 52% had unsatisfactory hygienic-sanitary quality for the parameters evaluated.